Disminución de las ventas de la Empresa Vihalmotos Importaciones S.A. de la ciudad de Ambato, en el periodo 2021. - Alvarado Maldonado, Marcela Nahomi (2022)
Vihalmotos Importaciones S.A. began commercial activities on December 6, 2002 with RUC number 189170936001, represented by Mr. Alvarado Lascano Víctor Hugo. It is located in the city of Ambato on Galileo Galet street Vía A Tangaiche Av. Los Pericos Edif Vihal. In their regular analyzes of their financial performance, they discovered a decrease in the sales volume of their products in 2021 compared to 2020. The company had problems with sales, planning, management, they do not have a specific business goal or strategy for eliminate, customer retention, has also undergone drastic changes thanks to the entry of entrepreneurs with great financial capacity, has raised the level of competition and has helped reconfigure the preferences of those who, for various reasons, frequent this importer. The methodology for advancing the case study consists of applying the qualitative method because the case is going to be analyzed theoretically; quantitative because numerical data and calculations will be used using financial ratios of profitability through the use of Financial Statements. Management has concentrated on trying to meet the organization's offering with a series of innovations. However, sales are down, some regular customers are not coming back, and this goes hand in hand with the increased competition in the industry and the difficulties businesses are facing. This work will try to know the causes and their impact on the profitability of Vihalmotos Importaciones S.A, in order to suggest certain guidelines according to the experts or authors related to the research topic.